Momento crítico hacia la identidad cultural del habitante santarroseño Melero mediante el arte contemporáneo - Ramos Montero, Luis Ángel (2015)
For a better understanding of this research it has been divided into four chapters Chapter one refers to the historical background-of the-term Melero with which certain longstanding-santaroseños-was-called. -Also-globalization-has-influenced the loss of identity also, art and anthropology of gender as a fundamental part to dispel doubts about the issue at hand. Chapter two presents the drawing as part of the proposal will address how this technology and make it work as work time, based on the concept of Harold Rosenberg. Anxious objects and operate as art my proposal.